Estudo da influência do condicionamento higrotérmico nas propriedades viscoelásticas de compósitos termoplásticos - De Faria, Maria Cândida Magalhães [UNESP]; De Oliveira, Pedro Carlos; Ribeiro, Bruno [UNESP]; Martet, José Maria Fernandes; Botelho, Edson Cocchieri [UNESP] (FapUNIFESP (SciELO), 2017)
Continued growth in the use of thermoplastic composites for structural components in the aerospace industry due, primarily, to the design flexibility, excellent mechanical properties and low density, combined with the high values of strength and stiffness and low incidence of corrosion meeting the stringent performance requirements of these structures while in service. However, components that requires structural requirements when exposed to harsh environments such as high temperature and moisture, can have their mechanical properties reduced by these environmental factors, and should be carefully evaluated before being placed in service. Although there are several studies in the literature reporting this problem for structural composites, few studies relate in a systematic way, assessing the moisture absorption with the viscoelastic behavior of PPS matrix reinforced with carbon fibers, when the composite is used in aeronautical applications. Thus, the aim of this study is to evaluate the influence of hygrothermal conditioning on the viscoelastic properties of PPS/carbon fiber composites. The results show that the laminates conditioned in a hygrothermal chamber had moisture absorption according to Fick laws, but it was not observed a significant glass transition temperature variation when compared conditioned and not conditioned specimens.
Study of the influence on higrothermal conditioning on viscoelastic properties of thermoplastic composites
Keywords: Hygrothermal effect; Mechanical properties; Thermoplastic composites